Biogeographical signature of river capture events in Amazonian lowlands - Tagliacollo, Victor A. [UNESP]; Roxo, Fábio Fernandes [UNESP]; Duke-Sylvester, Scott M.; Oliveira, Claudio [UNESP]; Albert, James S. (Wiley, 2015)
Aim: To investigate the effects of river capture on the biogeographical history of South American freshwater fishes. Location: Western Amazon and La Plata basins, and adjacent river drainages. Methods: We used a species-dense time-calibrated phylogeny of long-whiskered catfishes (Siluriformes, Pimelodidae) to calculate likelihoods for 16 biogeographical scenarios of river capture, each differing in details of (1) landscape evolution and/or (2) models of species range evolution. We designed eight alternative landscape evolution models (LEMs) to represent distinct palaeogeographical river capture histories between the Western Amazon and La Plata drainages during the formation of the Central Andean (Bolivian) orocline (43.0-15.0 Ma). The LEMs differed only in patterns of area-connectivity constraints through time, and otherwise had the same geographical areas, time durations and dispersal probabilities. We used the DEC and DECj models of species range evolution under these eight LEM constraints to calculate likelihood values for ancestral area estimates. Results: Divergence time estimates indicated that crown-group pimelodids emerged during the Late Cretaceous or Palaeogene (c. 72.9 ± 20 Ma) and model-selection recovered a best-fit palaeogeographical scenario with (1) a LEM with three river capture events, and (2) a DECj model of species range evolution. These results were quantitatively replicated using Lagrange and BayArea-like methods. Main conclusions: The taxon-area chronogram of pimelodids exhibits the characteristic biogeographical signature of river capture; i.e. several non-monophyletic regional (basin-wide) species assemblages coupled with the presence of many species inhabiting more than one basin. These phylogenetic and biogeographical patterns are consistent with the effects of three large-scale river capture events during the formation of the Bolivian orocline.
Keywords: Amazonian biodiversity; Geographical range evolution; Historical biogeography; Landscape evolution models; Neotropical fishes; Parametric biogeography; Pimelodidae; River capture